Analysis of butter supply chain: the case of Atsbi-Wenberta and Alamata Woredas, Tigray, Ethiopia - Kidanu, E. (Haramaya University, 2010)
Butter is an important source of food, cosmetics and common marketable form of dairy product in the study areas. The total butter production in the survey year was 18880 kg in both the woredas, out of which 87.6% was supplied to market. The objective of this study is to investigate the butter supply chain in Atsbi-wonberta and Alamata woredas of Tigray region. The specific objectives were to analyze production and marketing supporting services, to identify structure of production costs and determine profitability, to analyze determinants of butter supply, to analyze structure-conduct and performance of butter market and to identify major production and marketing constraints and opportunities. To accomplish these tasks formal and informal data collection tools of both primary and secondary data were used. a survey was conducted in the districts in which data was collected from randomly selected 200 butter producer households of Atsbi and Alamata woredas using a structured questionnaire and from 56 butter traders at different level of the chain from Alamata, Atsbi and the terminal market, Mekelle. The econometric result of market participation decision indicated quantity produced, number of extension visit, market information access, family size, distance to nearest market and distance to development center are the significant factors. Similarly, quantity produced, distance to nearest market and distance to development center are significant factors affecting level of supply. As to the probit model of determinants of access to crossbreed cows; number of extension visit, participation in extension demonstration, access to veterinary service and distance to the woreda town are significant factors. Likewise, dairying experience, labor availability, distance to feed market and access to formal credit are significant factors determining farmers’ access to feed in the probit model. Among the hypothesized determinants of access to cattle drug; number of extension visit, number of cows and distance to the nearest market found to be significant factors. The probit model of households’ credit constraint condition reveals herd size, distance to development center, off farm income and frequency of extension contact are the significant factors associated with credit constraint condition. The net returns, generated after deducting all economic cost of resources used for butter production, found to be 1623ETB per cow/year from crossbreed cows and 213ETB per cow/year from local breed cows with overall average net return of 918.3ETB per cow annually. Following the market structure criteria of concentration ratio, butter market shows competitive nature in Atsbi market with C4 of 31%, and weak oligopolistic nature in Alamata and Mekelle markets as their concentration ratios are 39% and 44% respectively. Entry barriers were not observed in relation to licensing and working capital. However, considerable burrier was observed with respect to years of experience at the wholesale level and risk of seasonal variation in demand and price of butter. Based on the channel comparison and marketing margin analysis of butter market performance, the producer’s share of the consumer’s price was found to be the highest along producer-consumer channel followed by producer-woreda retailer-consumer and producer-rural assembler-wholesaler-consumer. The major constraints of butter production and marketing in the studied areas were inadequate availability and supply of feed, the low productivity of the endogenous cattle breeds, low supply of crossbreed cows, lower demand of butter during fasting periods, adulteration and seasonal fluctuation of butter price. Therefore, taking into account these factors in designing butter production and marketing improvement programme may help policy makers come up with policies aimed at ameliorating the butter supply chain in the districts.